Corporate social responsibility (CSR) performance and stakeholder engagement: evidence from the quantity and quality of CSR disclosures - Koh, Kevin (2022)
With increasing stakeholders' demand for information on corporate social responsibility (CSR) performance and a growing number of firms issuing standalone CSR reports, this study examines the relation between CSR performance and the quantity and quality of CSR disclosures. Drawing on signaling and political legitimacy theories of information disclosure and using a US sample of 2774 standalone CSR reports from 2003 to 2015, we find better CSR performing firms issue longer CSR reports and provide incremental information in their CSR reports relative to their annual financial reports. Furthermore, the textual content in their CSR reports is less focused on short-term issues, reflecting higher disclosure quality. In contrast, poor CSR performing firms tend exhibit lower disclosure quality as their CSR reports use more uncertain words. Our study contributes to the understanding of how CSR performance affect stakeholder engagement through the characteristics of textual content in standalone CSR reports.